Anti-Inflammatory Effect of Procyanidins from Wild Grape (Vitis amurensis) Seeds in LPS-Induced RAW 264.7 Cells. (23rd October 2013) - Bak, Min-Ji; Truong, Van Long; Kang, Hey-Sook; Jun, Mira; Jeong, Woo-Sik
Abstract : In the present study, the anti-inflammatory effect and underlying mechanisms of wild grape seeds procyanidins (WGP) were examined using lipopolysaccharide- (LPS-) stimulated RAW 264.7 cells. We used nitric oxide (NO) and prostaglandin E2 (PGE2 ) and reactive oxygen species (ROS) assays to examine inhibitory effect of WGP and further investigated the mechanisms of WGP suppressed LPS-mediated genes and upstream expression by Western blot and confocal microscopy analysis. Our data indicate that WGP significantly reduced NO, PGE2, and ROS production and also inhibited the expression of proinflammatory mediators such as inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) protein expressions. Consistently, WGP significantly reduced LPS-stimulated expression of proinflammatory cytokines such as tumor necrosis factor α (TNF- α ) and interleukin- (IL-) 1 β . Moreover, WGP prevented nuclear translocation of nuclear factor- κ B (NF κ B) p65 subunit by reducing inhibitory κ B- α (I κ B α ) and NF κ B phosphorylation. Furthermore, we found that WGP inhibited LPS-induced phosphorylation of p38 mitogen-activated protein kinase (MAPK). Taken together, our results demonstrated that WGP exerts potent anti-inflammatory activity through the inhibition of iNOS and COX-2 by regulating NF κ B and p38 MAPK pathway.